For God, King, and Country: Nineteenth-Century Methodist Interpretations of the War of 1812 (The London Journal of Canadian Studies, 2014)
The War of 1812 almost ruined Episcopal Methodism in Upper Canada. During the War, the American itinerants were unable to travel in the land and, after the War, their detractors used their connection to America to undermine their influence in the loyal Province. This article offers two examples in order to highlight the ways in which the Methodists themselves used the war to prove their loyalty as well as their role in developing the land that would one day become Canada. The first example looks at how Methodists in the Reform party of the 1828 House of Assembly viewed their denomination’s role during and in the years following the War. The second example looks at the publication of two popular books in 1880 that defended the contribution American Methodists had made to the British war effort. These examples moved the issue of Methodist loyalty into the sphere of politics and public policy and showed how the ongoing interpretation of the War of 1812 continued to affect these Methodists throughout the nineteenth century.